Mortality of seabirds during "El Niño 1997-98" in southern littoral of San Juan of Marcona, Ica -Peru - Apaza, Manuel (1999)
The death rate of seabirds population at southern guano Point of San Juan of Marcona was evaluated among August of 1997 and April of 1998. Species of exclusively pelagic feeding, and restricted distribution to the scope of Peruvian Current, as guano birds Pelecanus thagus, Sula variegata, and Phalacrocorax bougainvillii; the Humboldt penguin Spheniscus humboldti, and the Inca tern Larosterna inca showed a significant correlation in monthly behave. It is related with sea surface temperature and with the absent of anchovy Engraulis ringens during "El Niño" event. Other species considered in the analysis showed a different death-rate, as Franklin's sea-gull Larus pipixcan and gray sea-gull Larus modestus, in both cases the species fed of alternative resources as Cafosoma sp. and Emerita analoga, respectively.